Development of an ELAA kit to detect neomycin in milk - Truong Giang, Nguyen; Thi Bich Dao, Tran; Quang Huan, Le; Thi Huyen, La (Vietnam Journal of Biotechnology, 2021)
Antibiotics used in livestock production offer various benefits as an antimicrobial agent, growth promoter, and feed effective improvement. However, the abuse of antibiotics leads to antibiotic resistance which may seriously threaten human and animal welfare, and growing levels of antibiotics or antibiotic-resistant bacteria in the environment increase the numbers of drug-resistant infection outbreaks. Therefore, many detection methods have been being developed to quickly assess antibiotic content and its residues in foods. Among many analytical methods, the aptamer-based biosensor has considerable attention for its outstanding advantages such as high specificity, high sensitivity, and good selectivity. We use the ELAA (Enzyme-Linked Aptamer Assay) method - a variant of ELISA - which has a high affinity with neomycin. Firstly, we investigated different buffers to create the Neo-BSA complex. As result, 2-(N-morpholino) ethanesulfonic acid (MES) buffer pH 7 was found with the best results. Next, to help the Neo-BSA complex be fixed well on polystyrene wells, we surveyed various buffers and found the coating buffer (50mM Bicarbonate buffer, pH 9.6) rated as the most suitable for this process. In addition, the quality of the kit is also assessed through competitive ELAA reaction components. Therefore, we have investigated and optimized conditions such as aptamer concentration 25 nM in PBS buffer, and the biotinized aptamers did not need heat treatment prior to joining the reaction. From the results, we have successfully developed a calibration curve for antibiotic residue in milk using the ELAA technique, linear range 0,1 ng/mL and 100 ng/mL. Then, we initially surveyed 20 milk samples found that the ELAA method was consistent with the results from LC-MS/MS was obtained showing no difference between the two methods. We continued to test the samples to determine the kit’s sensitivity and specificity. The results showed that the kit has a specificity and sensitivity of 100%. Finally, LOD and LOQ value had xavg = 0.448; SD = 0.22, LOD = xavg + 3SD = 1.11 (ng / ml); LOQ = x tb + 10SD = 2.65 (ng / mL). We will continue to optimize the kit before being brought to the market.